Learning Under Fire: Adult Education in the Heat of Conflict - R. Michael Fisher (Adult Education Research Conference, 2000)
A critical review of the discourses on ‘conflict’ in conflict management education literature revealed an ideological bias and "hidden curriculum" of propaganda, which is heavily influencing social conflict conceptualizations and practices. Workers with adults have an emerging 'conflict' pedagogy to develop and draw upon as counterhegemonic. Conflict is re-examined as a critical site of learning.